Analisis Pengawasan Pembiayaan Mudharabah pada Produk Mikro Syariah di BMT Tamzis Cabang Bandung - Salsabila Rafidah; Zaini Abdul Malik; Intan Manggala Wijayannti (UNISBA Press, 2024)
Abstract. Baitul Maal Wattamwil (BMT) is a microfinance institution whose operations are based on sharia principles. Financing in BMT involves the provision of funds by the institution to the community which must be returned in accordance with established sharia principles. Supervision is the process of observing all organizational activities. One of the sharia microfinance products owned by BMT Tamzis, especially in the mudharabah contract, has reached 600 members. Therefore, researchers are interested in knowing the suitability of supervision of Islamic microfinance products at BMT Tamzis. This study aims to analyze the mechanism and implementation of financing supervision on these products at BMT Tamzis Bandung. The research method used is qualitative with a normative juridical approach and uses a type of field research. Data were obtained through observation, interviews, literature studies, documentation, and analyzed using qualitative descriptive techniques. Research findings show that there are several factors that cause the lack of implementation of the supervision system with established SOPs. These factors include: the supervisory team only consists of account officers and marketing collectors, while supervision should involve various parties such as DPS, the finance team and the financing committee team. Not effective in the ball pickup system and the number of officers is less when compared to the number of customer members. Budget limitations for travel money. Lack of awareness of customer members paying financing installments. Then the lack of participation of customer members in the coaching program that has been organized by BMT Tamzin. Abstrak. Baitul Maal Wattamwil (BMT) adalah lembaga keuangan mikro yang operasionalnya berlandaskan prinsip syariah. Pembiayaan di BMT melibatkan pemberian dana oleh lembaga kepada masyarakat yang harus dikembalikan sesuai dengan prinsip syariah yang ditetapkan. Pengawasan merupakan proses pengamatan terhadap seluruh kegiatan organisasi. Salah satu produk pembiayaan mikro syariah yang dimiliki oleh BMT Tamzis, khususnya pada akad mudharabah telah mencapai 600 anggota. Oleh karena itu, peneliti tertarik untuk mengetahui kesesuaian pengawasan terhadap produk pembiayaan mikro syariah di BMT Tamzis. Penelitian ini bertujuan untuk menganalisis mekanisme dan implementasi pengawasan pembiayaan pada produk tersebut di BMT Tamzis Bandung. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan yuridis normatif dan menggunakan jenis penelitian lapangan. Data diperoleh melalui observasi, wawancara, studi pustaka, dokumentasi, dan dianalisis menggunakan teknik deskriptif kualitatif. Temuan penelitian menunjukkan adanya beberapa faktor yang menyebabkan kurangnya implementasi sistem pengawasan pembiyaan dengan SOP yang telah ditetapkan. Faktor-faktor tesebut meliputi : tim pengawas hanya terdiri account officer dan marketing kolektor saja, sementara seharusmya pengawasan harus melibatkan berbagai pihak seperti DPS, tim keuangan dan tim komite pembiayaan. Tidak efektif dalam sistem jemput bola dan jumlah petugas terbilang kurang jika dibandingkan dengan jumlah anggota nasabah. Keterbatasan anggaran biaya untuk uang perjalanan. Kurangnya kesadaran para anggota nasbah membayar angsuran pembiayaan. Kemudian kurangnya partisipasi anggota nasabah dalam program pembinaan yang telah diselenggarakan oleh BMT Tamzis.